Association of inflammation and protein carbamylation in patients with COVID-19 - Smykiewicz, Jolanta; Tomasiuk, Ryszard; Cemaga, Roman; Buczkowski, Jakub; Maciejczyk, Mateusz (Frontiers in Medicine, 2025)
IntroductionCarbamylation involves the non-enzymatic binding of isocyanic acid to the amino groups of proteins, making it associated with many pathological conditions, including inflammation, aging, arteriosclerosis, and renal failure. However, there are no data on protein carbamylation in patients with COVID-19. Our study is the first to evaluate the association between blood inflammation and protein carbamylation in patients who died from COVID-19 compared to COVID-19 survivors.MethodsThe study included 50 patients admitted to Dr. Tytus Chałubiński Specialist Hospital in Radom, Poland. Twenty-five of them were COVID-19 survivors (15 men, 10 women), and 25 were COVID-19 deceased patients (15 men, 10 women). The number of subjects was based on a pilot study assuming a significance level of 0.05 and a test power of 0.8. Plasma/serum samples were assayed for carbamyl-lysine (CBL) and inflammatory biomarkers (CRP, procalcitonin, D-dimer, IL-6, and WBC). The concentration of CBL was measured using an enzyme-linked immunosorbent assay (ELISA). Statistical analysis was performed using the Mann-Whitney U test and Spearman rank correlation. Receiver Operating Characteristic (ROC) analysis was used to assess the diagnostic utility of serum CBL.ResultsSerum CBL levels were significantly higher in patients who died from COVID-19 compared to COVID-19 survivors (p = 0.0011). There was a positive correlation of serum CBL with IL-6, D-dimer, and WBC. Serum CBL levels >101 ng/mL, with moderate sensitivity and specificity, differentiate COVID-19 deceased from recovered patients (area under the curve 0.76).DiscussionIn conclusion, COVID-19 is associated with excessive protein carbamylation. Inflammation may be a source of higher CBL production in COVID-19. A thorough understanding of the consequences of increased protein carbamylation may clarify the consequences of COVID-19 complications.